2016
DOI: 10.1038/ncomms13965
|View full text |Cite
|
Sign up to set email alerts
|

Ecological networks are more sensitive to plant than to animal extinction under climate change

Abstract: Impacts of climate change on individual species are increasingly well documented, but we lack understanding of how these effects propagate through ecological communities. Here we combine species distribution models with ecological network analyses to test potential impacts of climate change on >700 plant and animal species in pollination and seed-dispersal networks from central Europe. We discover that animal species that interact with a low diversity of plant species have narrow climatic niches and are most v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
225
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 211 publications
(246 citation statements)
references
References 55 publications
(98 reference statements)
4
225
1
1
Order By: Relevance
“…The dominant grass species at KPBS, Andropogon gerardii , decreases in biomass at soil temperatures >25°C (DeLucia, Heckathorn, & Day, ). Based on previously reported plant community responses (Harrison, Gornish, & Copeland, ) and our results, increasing temperatures decrease plant species richness in this system, making grasshopper communities more susceptible to additional plant loss (Schleuning et al, ) and decreasing grasshopper diversity (Lenhart et al, ). High temperatures may also directly reduce grasshopper populations if species pass thermal limits; a previous temperature manipulation study on KPBS showed grasshopper survival in the absence of predators was highest in the lowest temperature treatment (Laws & Joern, ).…”
Section: Discussionsupporting
confidence: 80%
“…The dominant grass species at KPBS, Andropogon gerardii , decreases in biomass at soil temperatures >25°C (DeLucia, Heckathorn, & Day, ). Based on previously reported plant community responses (Harrison, Gornish, & Copeland, ) and our results, increasing temperatures decrease plant species richness in this system, making grasshopper communities more susceptible to additional plant loss (Schleuning et al, ) and decreasing grasshopper diversity (Lenhart et al, ). High temperatures may also directly reduce grasshopper populations if species pass thermal limits; a previous temperature manipulation study on KPBS showed grasshopper survival in the absence of predators was highest in the lowest temperature treatment (Laws & Joern, ).…”
Section: Discussionsupporting
confidence: 80%
“…The positive association between resource and consumer diversity underpins the relevance of bottom-up effects in ecological communities. One important implication of this finding is that the loss of plant diversity, e.g., due to forest conversion, selective logging or climate change, could have cascading effects on the associated animal communities (Brodie et al, 2014;Schleuning et al, 2016). In contrast to the bottomup effects of plants on animals, the PD and functional identity of bird dispersers were unrelated to the PD and functional identity of seedlings.…”
Section: Resultsmentioning
confidence: 52%
“…nitrophilous plants, Chapin 1980), or if some parts of the plants (e.g. global domino effect; Schleuning et al 2016, Pöyry et al 2017). For instance, why are declines at coarse scales more accentuated for bees that were specialized on nitrophilous plants (Fig.…”
Section: Effect Of Resource Preferences On Historical Patterns Of Biomentioning
confidence: 99%